1984
DOI: 10.1177/107110078400500103
|View full text |Cite
|
Sign up to set email alerts
|

Heel Pain—Operative Results

Abstract: In 6 years through 1982, the authors performed 34 operative cases in 26 patients with recalcitrant heel pain. The operative procedure involves an isolated neurolysis of the mixed nerve supplying the abductor digiti quinti muscle as it passes beneath the abductor hallucis muscle and beneath the medial ridge of the calcaneus. The deep fascia of the abductor hallucis muscle is released routinely, and an impinging heel spur or tight plantar fascia is partially removed or released if it is causing entrapment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
13

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(89 citation statements)
references
References 14 publications
1
75
0
13
Order By: Relevance
“…Although plantar fasciitis may resolve after a few weeks, in some patients symptoms may become chronic. The best management of chronic plantar fasciitis is not entirely agreed upon and a variety of conservative approaches as well as more invasive treatments has been suggested (13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Although plantar fasciitis may resolve after a few weeks, in some patients symptoms may become chronic. The best management of chronic plantar fasciitis is not entirely agreed upon and a variety of conservative approaches as well as more invasive treatments has been suggested (13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…This condition was considered to be rare. In the 1980's the identification of the lateral plantar nerve and its branches by Baxter and colleagues confirmed that the nerve could be entrapped at other sites [4]. In these individuals where the lateral plantar nerve or the calcaneal branch of the lateral plantar nerve is affected, patients can present with heel pain.…”
Section: Introductionmentioning
confidence: 83%
“…Tedavide; uzunlamasına ark destekleyici ortezlerden, alçıya ve cerrahi tedavilere kadar çeşitli seçenekler mevcuttur. [17] Sedanter kişilerde konservatif yöntemler daha yoğun olarak tercih edilmektedir. Atletlerde ise tedavi yaklaşımları farklılık arz eder.…”
Section: Tedavi̇unclassified